Gregariousness in the giant sloth Lestodon (Xenarthra): multi-proxy approach of a bonebed from the Last Maximum Glacial of Argentine Pampas - Tomassini, Rodrigo Leandro (2020)
Megamammals constituted an important component in the Pleistocene faunal communities of South America. Paleobiological and paleoecological studies involving different megamammal taxa have increased significantly in the last years, but there are still several poorly-known issues of its life history. In this work, we analyze an assemblage composed of 13 individuals of different ontogenetic stages, and possibly different sex, belonging to the giant ground sloth Lestodon armatus (Xenarthra, Folivora), recovered from Playa del Barco site (Pampean Region, Argentina). A dating of 19,849 years Cal BP allows assigning this assemblage to a period of the MIS (Marine Isotope Stage) 2 related to the end of the Last Glacial Maximum. Based on multiple lines of research (e.g. taphonomy, paleopathology, osteohistology, isotopy), we interpret the origin of the assemblage and diverse paleobiological and paleoecological aspects (e.g. social behavior, ontogenetic changes, sexual dimorphism, diseases, resource and habitat use, trophic relationships) of L. armatus. Evidence suggests that the assemblage was formed by a local single event of catastrophic mortality, which affected different members of a social group. This record represents the first accurate evidence of gregariousness for this ground sloth, providing new data on a poorly-known behavior among extinct Folivora.